PENGARUH KOMPETENSI, INDEPENDENSI, DAN KEMAHIRAN PROFESIONAL TERHADAP KUALITAS AUDIT YANG DIMODERASI OLEH AKUNTABILITAS - William Jonathan; Hendang Tanusdjaja (Fakultas Ekonomi Universitas Tarumanagara, 2022)
This study aims to examine the effect of competence, independence, professional skills on audit quality withaccountability. Primary data is the data used in this study. 85 questionnaires were distributed in which 47questionnaires were distributed directly and 38 questionnaires with the help of Google form. The questionnairesreturned and were used were 83 questionnaires. Data processing was performed using logistic regression analysismethod using SPSS version 25. The results obtained from this study indicate that competence and independence donot have a positive influence on audit quality. Meanwhile, professional skills have a positive influence on auditquality. The results of this study also concluded that accountability does not moderate the effect of competence,independence and professional skills on audit quality